Precise tuning of the Curie temperature of (Ga,Mn)As-based magnetic semiconductors by hole compensation: Support for valence-band ferromagnetism - Zhou, Shengqiang; Li, Lin; Yuan, Ye; Rushforth, A.W.; Chen, Lin; Wang, Yutian; Böttger, R.; Heller, R.; Zhao, Jianhua; Edmonds, K.W.; Campion, R.P.; Gallagher, B.L.; et al. (American Physical Society, 2016)
For the prototype diluted ferromagnetic semiconductor (Ga,Mn)As, there is a fundamental concern about the electronic states near the Fermi level, i.e., whether the Fermi level resides in a well-separated impurity band derived from Mn doping (impurity-band model) or in the valence band that is already merged with the Mn-derived impurity band (valence-band model). We investigate this question by carefully shifting the Fermi level by means of carrier compensation. We use helium-ion implantation, a standard industry technology, to precisely compensate the hole doping of GaAs-based diluted ferromagnetic semiconductors while keeping the Mn concentration constant. We monitor the change of Curie temperature (TC) and conductivity. For a broad range of samples including (Ga,Mn)As and (Ga,Mn)(As,P) with various Mn and P concentrations, we observe a smooth decrease of TC with carrier compensation over a wide temperature range while the conduction is changed from metallic to insulating. The existence of TC below 10 K is also confirmed in heavily compensated samples. Our experimental results are naturally explained within the valence-band picture.